Social Capital, Political Participation and Migration in Europe 2011
DOI: 10.1057/9780230302464_1
|View full text |Cite
|
Sign up to set email alerts
|

Political Opportunities, Social Capital and the Political Inclusion of Immigrants in European Cities

Abstract: Discussions about how public policies can promote more effectively the active engagement and participation of immigrants and their children1 in the political and civic life of the countries where they live are at the core of current scholarly and public debates. In advanced democracies, there are recurrent disputes about the appropriateness and potential benefits or shortcomings of introducing legal reforms that would guarantee that large immigrant populations — and especially their native-born children — are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 0 publications
3
27
0
1
Order By: Relevance
“…In a study of immigrant political participation in Europe (across a set of European cities), migrants' organizations, civil society groups, and consultative bodies provide higher levels of social capital that encourage participation among immigrants (bonding and group mentalities among immigrants) (Morales & Giugni, ). In this edited volume, Gonzalez‐Ferrer () compared members of immigrant communities who either naturalized or were from Europe and found that in the cities where immigrants were given a stable legal status (relaxed rules regarding residency permits), naturalized immigrants were more likely to vote in comparison to cities with tougher naturalization rules.…”
Section: The Relationship Between Discrimination and Political Particmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of immigrant political participation in Europe (across a set of European cities), migrants' organizations, civil society groups, and consultative bodies provide higher levels of social capital that encourage participation among immigrants (bonding and group mentalities among immigrants) (Morales & Giugni, ). In this edited volume, Gonzalez‐Ferrer () compared members of immigrant communities who either naturalized or were from Europe and found that in the cities where immigrants were given a stable legal status (relaxed rules regarding residency permits), naturalized immigrants were more likely to vote in comparison to cities with tougher naturalization rules.…”
Section: The Relationship Between Discrimination and Political Particmentioning
confidence: 99%
“…They found this correlation in Scandinavian cities (Oslo and Stockholm), and they conclude that they did not find clear evidence that discrimination spills over into participation. Morales and Giugni () examined political participation across Barcelona, Madrid, Milan, Lyon, Oslo, Stockholm, and Zurich. They did not find a correlation between those who report discrimination and participation.…”
Section: The Relationship Between Discrimination and Political Particmentioning
confidence: 99%
“…3 Until the Spanish National Immigrant Survey was conducted in 2007, there was no comprehensive survey information on the immigrant population in Spain (see chapter 3 in this volume). 4 The samples are described in greater detail in Morales and Giugni (2011). 5 However, see , Keeter et al (2000) and Keeter et al (2006) for illustrations of how substantially different response rates due to varying fieldwork strategies need not bias the distribution of responses on a number of attitudinal and behavioural indictors.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Scholarly research on the political representation of immigrant minorities has gained greater attention with the transition of former outsiders into full citizens (among others, see Bird et al., 2011; Morales and Giugni, 2011). Indeed, there are legitimate grounds for that to be the case.…”
Section: Introductionmentioning
confidence: 99%